Effects of turning rainforest into oil-palm plantations on silicon pools in soils within the first 20 years after the transformation - Greenshields, Britta; von der Lühe, Barbara; Hughes, Harold; Tjoa, Aiyen; Hennings, Nina; Sauer, Daniela (Frontiers in Environmental Science, 2023)
Potential effects of land-use/land-cover (LULC) transformation from lowland rainforest into oil-palm plantations on silicon (Si) pools in tropical soils remain poorly understood, although appropriate levels of plant-available Si in soils may contribute to maintain high crop yields and increase the vitality and drought resistance of oil palms. Therefore, the aim of our study was to identify possible effects of such LULC change on soil Si pools. For this purpose, we compared soil Si pools under lowland rainforest and ca. 20 year-old oil-palm plantations in Jambi Province, Indonesia. The investigated soils were Acrisols and Stagnosols, in which we quantified six different soil Si pools following a sequential extraction procedure to evaluate, whether 20 years of oil-palm cultivation has led to a depletion of these soil Si pools. The considered pools included mobile Si, adsorbed Si, Si bound in soil organic matter (SOM), Si included in pedogenic oxides and hydroxides, and Si in amorphous silica of biogenic and pedogenic origin. Finally, we also determined total Si. All oil-palm plantations established on sloping terrain and Acrisols only showed decreased Si stocks of mobile Si, adsorbed Si and SOM-bound Si; those established in floodplains and Stagnosols had decreased stocks of SOM-bound Si and biogenic-amorphous silica. Lower Si stocks were mostly attributed to a missing “stable” phytolith pool in the subsoil and less organic matter in topsoils under oil-palm plantations. When comparing well-drained and riparian areas, flooding seemed to increase phytolith dissolution. We conclude that 20 years of oil-palm cultivation has not yet led to a significant depletion of soil Si pools. As topsoils comprise the highest concentrations of SOM-bound Si and Si in amorphous silica of biogenic origin but are susceptible to erosion and surface runoff under managed oil-palm plantations, it would be advisable to instate specific management practices that maintain organic-rich and well-aired topsoils on oil-palm plantations.